Cooperation and conflict at the horn of Africa: a new regional bloc between Ethiopia, Eritrea, and Somalia and its Consequences for Eastern Africa - Henneberg, Ingo; Stapel, Sören (2020)
Abstract: In January 2020, Eritrea, Ethiopia, and Somalia proposed to form a new regional bloc, occasionally referred to as the Horn of Africa Cooperation (HoAC). This article assesses which factors have contributed to making this proposal and contemplates potential effects for the complex security challenges, political tensions among the neighbours, and existing institutional environment in the region. Drawing on the scholarship on comparative regionalism and overlapping regionalism, we show that a genuine interest to independently address security challenges in the Horn of Africa, as well as domestic concerns, are core motivations for the leaders in all three states. However, the HoAC proposal bears the risk of further alienating partners in the region and undermning security efforts of other regional organisations, most importantly the Intergovernmental Authority on Development, the African Union, and the Eastern Africa Standby Force. Thus, the promises and pitfalls of this new bloc could shape the regional architecture and cause new political challenges in the region